Intraoperative Cerebral Oximetry In Open Heart Surgeries Reduced Postoperative Complications: A Retrospective Study. - Norsham Juliana ,; Noor Anisah Abu Yazit,; Suhaini Kadiman,; Kamilah Muhammad Hafidz ,; Sahar Azmani ,; Nur Islami Mohd Fahmi Teng ,; Srijit Das (plos, 2024)
Indexed by WOS/Scopus/ERA